Horace’s Odes 1.3, Elpino Duriense’s two translations, and two Portuguese imitations of the sixteenth century - Hasegawa, Alexandre Pinheiro (2021)
In this article I intend to discuss the presence of Horace’s Odes 1.3 in Portuguese Literature, in particular in two translations of Elpino Duriense and in two Portuguese poets of the sixteenth century, namely Antônio Ferreira (Odes 1.6) and Luís de Camões (Os Lusíadas 4.102-104). Although Odes 1.3 was perceived to be immature by some scholars, the poem was translated into Portuguese since the sixteenth century and imitated since Antiquity. Some Portuguese imitations stand out in Portuguese Literature and Elpino Duriense has that of Antônio Ferreira as a model for one of the two translations.